The State of community newspapers in Sorsogon a case study - Botial, Angela Kristine D.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
In a fast-developing province such as Sorsogon, community newspapers can fulfill crucial roles as information disseminators and shapers of opinion. Their localized nature allows them to get in touch with the needs, interests, problems, and issues unique to the community. These conceptions provide the rationale for this study on the current state of community newspapers in the province of Sorsogon. A field survey questionnaire was sent to the editors or publishers of six publications included in this study. Only five responded while one newspaper was not reached because of its remote locality. The majority of the newspapers are newly founded, in tabloid format, published weekly and circulated in Sorsogon and neighboring provinces. Most are owned by individuals. The editors are male, mostly middle-aged, married Catholic. Plans for the papers include improving staff quality, production, and business management. A proposal to form an organization of local community newspaper was welcomed while a merger with another outfit was rejected. It may be inferred that the publishers - editors of these papers prefer to operate on their own but are not averse to coordinate and cooperate with their colleagues in an organization.
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Community newspapers, Sorsogon -- Philippines